Assessment of community pharmacists' knowledge, attitudes and their willingness to provide vaccination services in Saudi Arabia. - Abdulkarim M Meraya; Mamoon H Syed; Abdulwahab A Shabi; Huthaifa A Madkhali; Younis A Yatimi; Khalied Y Khobrani; Yahia A Mubarki; Amani Khardali; Hilal Thaibah; Ayesha Yasmeen (PLoS ONE)
Background Community pharmacists play an important role in increasing vaccination rates especially in countries where they offer vaccination services and administration. However, little is known about community pharmacist's willingness to provide vaccination services in Saudi Arabia. The objective of this study was to assess knowledge, attitudes, willingness and beliefs of community pharmacists in Saudi Arabia towards providing vaccines at pharmacies. Methods A cross-sectional, online questionnaire-based study using convenience sampling (Snowball technique) was used to obtain responses from community pharmacists across Saudi Arabia. The survey collected information on participants' demographics, knowledge about vaccine, attitude towards vaccine and their attitude to be immunization providers. Bivariate analysis and multiple linear regression models were employed to assess the relationships between demographic variables and outcomes. Results The study sample consisted of 384 community pharmacists. More than half of participants had poor knowledge about vaccines (54%). Only 8.4% of participants had good knowledge about vaccines. The results indicated that community pharmacists in the study sample have positive attitude toward vaccines and are willing to provide vaccination services. There was a significant relationship between knowledge about vaccine and attitude toward vaccines. Pharmacists with poor knowledge about vaccines had negative attitude toward vaccines as compared to those with high knowledge (β = -1.743; P-value = 0.024). Additionally, there was a significant relationship between knowledge about vaccine and attitude to be immunization providers. Pharmacists with poor knowledge about vaccines had negative attitude to be immunization providers as compared to those with high knowledge (β = -2.631; P-value = 0.002). Furthermore, a significant number of the community pharmacists reported facing critical barriers to provide vaccines including legal liability, lack of personal resources and lack of appropriate training. Conclusion Comprehensive training and certification programs for pharmacists are crucial to improve their competencies in handling and administering vaccines to increase the rate of vaccinations in Saudi Arabia.